2020
DOI: 10.1371/journal.pone.0238745
|View full text |Cite
|
Sign up to set email alerts
|

Oral sex practices among men who have sex with men and transgender women at risk for and living with HIV in Nigeria

Abstract: Background Men who have sex with men (MSM) and transgender women (TGW) are at risk for sexually transmitted infections (STIs), including those of the oropharynx. We estimated the prevalence and factors associated with oral sex practices and characterized oropharyngeal STIs among a cohort of MSM and TGW in Nigeria. Methods From 2013 to 2018, TRUST/RV368 recruited MSM and TGW into HIV/STI diagnosis and treatment at community-based clinics in Nigeria. Participants who completed HIV testing and oral sex questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Previous study has reported higher perceived HIV risk was associated with greater willingness to use PrEP (32). In Nigeria, MSM who engaged in oral sex have reported high prevalence of oropharyngeal STDs (33). Similarly, a study conducted by Templeton et al (34) revealed that MSM who often engaged in insertive oro-anal sex were more likely to have oropharyngeal gonorrhea than MSM who never engaged.…”
Section: Discussionmentioning
confidence: 95%
“…Previous study has reported higher perceived HIV risk was associated with greater willingness to use PrEP (32). In Nigeria, MSM who engaged in oral sex have reported high prevalence of oropharyngeal STDs (33). Similarly, a study conducted by Templeton et al (34) revealed that MSM who often engaged in insertive oro-anal sex were more likely to have oropharyngeal gonorrhea than MSM who never engaged.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a previous study reported that higher perceived HIV risk was associated with a greater willingness to use PrEP [ 37 ]. In Nigeria, MSM who engaged in oral sex reported a high prevalence of oropharyngeal STDs [ 38 ]. Similarly, a study conducted by Templeton et al [ 39 ] found that MSM who often engaged in insertive oro-anal sex were more likely to have oropharyngeal gonorrhea than MSM who never engaged in this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the internationally guided research in these countries has been in the context of sexually transmitted diseases such as HIV and Hepatitis, or raising awareness regarding the lesbian gay bisexual and transgender (LGBT) community. 39 – 43 …”
Section: Discussionmentioning
confidence: 99%
“…The citation analysis of these publications also shows that 8 out of the 10 most cited articles represent studies that have either reported the high prevalence of HIV or other sexually transmitted diseases among transgender and homosexual men in Muslim societies or raised awareness regarding HIV transmission and prevention. 39 – 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation